Dicationic imidazolium based ionic liquids: Synthesis and properties - Man, Zakaria (2017)
In the present work, four dicationic ionic liquids (DILs) having 1,1-Bis(3-methylimidazolium-1-yl) butylene ([C4(Mim)2]) cation with counter anions namely hydrogensulfate, methanesulfonate, trifluoromethanesulfonate, and paratoluene sulfonate were synthesized and characterized.